MENGUKUR KONTRIBUSI SISWA DALAM KEMACETAN KOTA - Mustofa, Mukhlis (Widya Wacana: Jurnal Ilmiah, 2015)
Student mobility in accessing education services is a consequence of children's rights. Theamount of fulfillment to use this transport proposition effect on the traffic conditions of a region.How effective ban on students bringing the motor to a standstill pengatasan city the mainproblem behind the high interest of local governments to prohibit driving this motorcycle. Thisstudent-based settings such vehicles, transport subsidy-based students, Application BOS studenttransportation and special attention on the part of school-related student transportation access